(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
At the beginning of the XXI century the main causes of death are recognized as non-communicable diseases. Among them the leading place is occupied by diseases of the circulatory system, from which about 17 million people die annually. In recent decades, ischemic heart disease is the main cause of mortality in most industrial countries of the world and, according to WHO, at the age of 50-54 years is 404-467 people per 100 thousand population [1,2].